Relationship between Evapotranspiration and Land Surface Temperature under Energy- and Water-Limited Conditions in Dry and Cold Climates - Zhigang Sun; Qinxue Wang; Ochirbat Batkhishig; Zhu Ouyang (Advances in Meteorology)
Remotely sensed land surface temperature- (LST-) dependent evapotranspiration (ET) models and vegetation index- (VI-) LST methods may not be suitable for ET estimation in energy-limited cold areas. In this study, the relationship of ET to LST was simulated using the process-based Simultaneous Heat and Water (SHAW) model for energy- and water-limited conditions in Mongolia, to understand the differences in ET processes under these two limiting conditions in dry and cold climates. Simulation results from the SHAW model along with ground observational data showed that ET and LST have a positive relationship when air temperature (Ta) is less than or equal to the temperature (Ttra) above which plants transpire and have a negative relationship when Ta is greater than Ttra under the energy-limited condition. However, ET and LST maintain a negative relationship with changes in Ta under the water-limited condition. The differences in the relationship between ET and LST under the energy-limited and water-limited conditions could be attributed to plant transpiration and energy storage in moist/watered soil and plants. This study suggests that different strategies should be used to estimate ET under the energy-limited condition in dry and cold climates.